2020
DOI: 10.1002/mabi.202000063
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Quaternary Ammonium Ionenes—Is There an Influence of Backbone Flexibility and Topology on Antibacterial Properties?

Abstract: The antimicrobial properties of polycations are strongly affected by the structural features such as the backbone flexibility and topology (isomerism) through the polymer ability to attain proper conformation in interaction with the cell membrane. In this paper, a synthesis and biocidal properties evaluation of ionenes characterized by different backbone topology (isomerism) and flexibility are presented. The findings reveal influence of variation in topology on activity against different microorganisms, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 78 publications
2
24
0
Order By: Relevance
“…These results point out that tailoring sequence structures rather than global composition of synthetic polycations may yield more specific biological outcomes akin to AMPs. In addition, the location of cationic moieties in the polymer chain also shows great impact on their biological activity. Especially when cationic moieties sit in the polymer backbone, they can present enhanced antibacterial activity and selectivity than those of corresponding polymers carrying cations as side groups . Encouraged by these findings, we designed and synthesized a new family of main-chain sulfonium-containing polymers with an AB-alternating sequence (Scheme ).…”
mentioning
confidence: 99%
“…These results point out that tailoring sequence structures rather than global composition of synthetic polycations may yield more specific biological outcomes akin to AMPs. In addition, the location of cationic moieties in the polymer chain also shows great impact on their biological activity. Especially when cationic moieties sit in the polymer backbone, they can present enhanced antibacterial activity and selectivity than those of corresponding polymers carrying cations as side groups . Encouraged by these findings, we designed and synthesized a new family of main-chain sulfonium-containing polymers with an AB-alternating sequence (Scheme ).…”
mentioning
confidence: 99%
“…Previous research has established that the alkyl chain length connected to the quaternary ammonium moieties, the position of QAS, and the hydrophobic/hydrophilic balance of the bactericidal components as the nature and flexibility of the polymeric matrix all contribute to the antimicrobial efficacy and cytocompatibility. Tuning the positive charge content and the amphiphilic balance has been introduced as a possible way of enhancing the antibacterial activity of QAS components. , An in-depth inspection of previous studies revealed that the QAS compound bearing a long hydrophobic chain exhibits a superior antibacterial efficiency. However, improving the antibacterial property through an increase in hydrophobicity might lead to an increase in cytotoxicity. , Hence, designing and engineering the structure of QAS components could provide potent antibacterial activity while minimizing toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Traditionally, the binary composition of cationic charge and hydrophobicity has been thought to be a minimal requirement for the antimicrobial mechanism of the antimicrobial polymers. Many efforts have been made to develop antimicrobial polymers based on different polymer backbones, such as methacrylate, 17,18 and optimize the monomer compositions and chemical identities of cationic and hydrophobic groups for potent antimicrobial activity and selectivity. [19][20][21] Recently, the approach has been extended to block copolymers with specic sequences, 22,23 branched polymers, [24][25][26] comb-like polymers, 27,28 polymer assemblies and micelles, 29,30 and single-chain polymer nanoparticles.…”
Section: Introductionmentioning
confidence: 99%